Cloning, Expression and Identification of the Enzyme P450-SCA12 from Streptomyces cavourensis YBQ59 - Thao, Nguyen Thi; Anh, Dao Thi Mai; Loan, Do Phuong; Thuy, Mai Thu; Bac, Vo Hoai; Trang, Nguyen Th Hien; Thuy, Ly Thi Bich (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 4, 2024)
The use of microbial cytochrome P450 as a biocatalyst offers significant potential for the development of natural compounds due to its ability to transform a wide range of structures with high regio- and stereoselectivity. In this study, a 1263 bp gene from S. cavourensis strain YBQ59, encoding the CYP154C subfamily enzyme P450-SCA12, was successfully expressed in E. coli CD43(DE3). The enzyme P450-SCA12 was produced in a soluble form when fused with thioredoxin (Trx) and 6xHis proteins from the pET32b(+) vector. After purification through ion affinity chromatography using a His-select® cobalt affinity gel column, the enzyme P450-SCA12 was obtained in an active form, with a molecular weight of approximately 63 kDa and a yield of around 1000 nmol/L from the Terrific Broth culture medium. Screening of substrates revealed that this enzyme specifically metabolizes three steroid compounds: testosterone, nandrolone, and 4-androstenedione. These findings highlight the potential of the P450-SCA12 enzyme from the actinomycete S. cavourensis YBQ59 in natural product development, particularly for metabolizing steroid compounds to create new steroid-based drugs.